2005
DOI: 10.1111/j.1471-4159.2005.03195.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired proteasome activity and accumulation of ubiquitinated substrates in a hereditary neuropathy model

Abstract: Western blot analysis (e) reveal that whereas the 30 kDa subunits remains unchanged (arrowheads), levels of the 25 kDa 20Sa and 20Sb subunits (arrows) are reduced in the TrJ, compared with Wt. GAPDH is shown as a constitutive marker. Molecular mass is given on the left, in kDa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 1 publication
3
32
0
Order By: Relevance
“…First, in contrast to MPZ and PMP22, Cx32 is not glycosylated and hence should not interact with the endoplasmic reticulum machinery that retains improperly glycosylated proteins. 44,49,52 In addition, unlike some MPZ mutants and most PMP22 mutants, 44,52,53 Cx32 mutants do not generate protein aggregates. 45 It remains to be determined whether endoplasmic reticulum-retained Cx32 mutants induce an unfolded protein response, 54 as do some MPZ mutants.…”
Section: Discussionmentioning
confidence: 92%
“…First, in contrast to MPZ and PMP22, Cx32 is not glycosylated and hence should not interact with the endoplasmic reticulum machinery that retains improperly glycosylated proteins. 44,49,52 In addition, unlike some MPZ mutants and most PMP22 mutants, 44,52,53 Cx32 mutants do not generate protein aggregates. 45 It remains to be determined whether endoplasmic reticulum-retained Cx32 mutants induce an unfolded protein response, 54 as do some MPZ mutants.…”
Section: Discussionmentioning
confidence: 92%
“…The Wt PMP22, a substrate for proteasomal degradation, is an aggregation-prone hydrophobic protein with a low folding efficiency (Pareek et al, 1997; Notterpek et al, 1999; Sanders et al, 2001). When one copy of the gene is mutated, the pool of PMP22 destined for the proteasome is increased, which leads to protein aggregate formation (Fortun et al, 2003; Fortun et al, 2005; Fortun et al, 2006). The accumulation of misfolded PMP22 within Schwann cells interferes with the activity of the ubiquitin-proteasome system (Bence et al, 2001; Fortun et al, 2005), and serves as a nucleation site for the aggregation of protein chaperones, such as HSP70 and αB-crystallin (Ryan et al, 2002; Fortun et al, 2005; Fortun et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…When one copy of the gene is mutated, the pool of PMP22 destined for the proteasome is increased, which leads to protein aggregate formation (Fortun et al, 2003; Fortun et al, 2005; Fortun et al, 2006). The accumulation of misfolded PMP22 within Schwann cells interferes with the activity of the ubiquitin-proteasome system (Bence et al, 2001; Fortun et al, 2005), and serves as a nucleation site for the aggregation of protein chaperones, such as HSP70 and αB-crystallin (Ryan et al, 2002; Fortun et al, 2005; Fortun et al, 2007). The entrapment of chaperones and proteasomal constituents within protein aggregates alters protein metabolic networks that function to ensure proper folding of newly-synthesized proteins, as well as the rapid degradation of misfolded proteins and short-lived regulatory molecules.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, aggresome-like structures have been identified in sciatic nerves of Tr J mice, surrounded by chaperones and lysosomes, suggesting that abnormalities in intracellular degradation of mutant PMP22 contribute to the pathogenesis of the neuropathy 83. More recent studies have shown that there are abnormalities of proteosome function resulting in the accumulation of ubiquitinated substrates in the Tr J model 84. Transfection studies have also demonstrated that other PMP22, as well as some MPZ mutations, result in mutant proteins being retained in intracellular compartments 85 86 87.…”
Section: Treatment Of Genetic Neuropathiesmentioning
confidence: 99%